Pengaruh Ukuran Perusahaan, Kompensasi Bonus dan Leverage Terhadap Manajemen Laba pada Perusahaan Manufaktur Sektor Industri Barang Konsumsi yang Terdaftar di Bursas Efek Indonesia Periode 2016-2018 - Ni Komang Rini Handayani; I Wayan Rupa; Sri Eka Jayanti (Program Studi Akuntansi, Fakultas Ekonomi, Universitas Warmadewa, 2020)
This study is entitled The Effect of Company Size, Bonus Compensation, and Leverage on Profit Management in Manufacturing Companies in the Consumer Goods Industry which are listed on the Indonesia Stock Exchange for the 2016-2018 Period. The formulation of the problem in this study is whether company size, bonus compensation, and leverage affect earnings management? This study aims to analyze empirically the effect of firm size, bonus compensation, and leverage on earnings management. The population in this study are Manufacturing Companies in the Consumer Goods Industry which are listed on the Indonesia Stock Exchange. The method of determining the sample in this study using purposive sampling method, and based on the specified criteria, the sample size is 26 companies. The data source in this study is secondary data obtained from the annual financial statements of companies listed on the Indonesia Stock Exchange for the period 2016-2018 by accessing www.idx.co.id. The analysis technique used is multiple linear regression analysis with SPSS application tools. The results of this study indicate that firm size has no effect on earnings management, bonus compensation has no effect on earnings management, and leverage has a negative and significant effect on earnings management.